Dias y dias = Days and days - Gibson, Ginger Foglesong; Moreno, Rene King (New York : Greenwillow Books, 2019)
Children enjoy being outside for every season. Whether rain, snow, or sunny days.
Keywords: Seasons -- Juvenile fiction